The Guidelines for Driving the Innovative Educational Area’s Schools through the PDCA Cycle of Educational Institutions under the Mae Yuam-Mae Khong Educational Administration Center, under the Mae Hong Son Primary Educational Service Area Office 2 - Aupakit, Teerasak; Kittiruchadanon, Suphaporn; Patthanameatada, Witthaya (Journal of Buddhist Education and Research (JBER), 2024)
Abstract This mixed-method research aimed to 1) study the conditions and problems of driving innovative education area schools through the PDCA cycle and 2) propose guidelines for driving innovative education area schools through the PDCA cycle in educational institutions within the Mae Yuam-Mae Khong Educational Administration Center, under the Mae Hong Son Primary Educational Service Area Office 2. The population included 182 school administrators and teachers from the Mae Yuam-Mae Khong Educational Administration Center and nine experts. Data were collected using questionnaires and interview forms and analyzed using frequency, percentage, mean, standard deviation, and content analysis. The findings indicated that the overall conditions of driving innovative education area schools through the PDCA cycle were at a high level (𝜇 = 3.82, 𝜎 = 0.47). Academic administration ranked the highest, followed by general administration, personnel administration, and budget management. Key problems included the lack of opportunities for teachers and educational personnel to communicate with network partners to acquire knowledge about educational innovation, the absence of computer resources for communication and educational technology development, and insufficient development of educational media, innovation, and technology to support transitions to the new normal. Recommended guidelines include providing computer resources for communication and innovation development by allocating an appropriate budget, organizing professional learning community activities to enhance teacher development, and establishing an information system to streamline activity management and workload.